Comparison of the Lipoamide Synthesis by Direct Amidation and via Amidation of Fatty Acid Methyl Esters - Chiko Harahap; Tuti Wukirsari; Sri Handayani; Sumi Hudiyono PWS (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
In this research, the preparation of lipoamide through direct amidation of fatty acid and via amidation of fatty acid methyl ester (FAME) was compared. The reactivity of aromatic amines and cyclohexylamine for the synthesis of lipoamide was investigated in this research. The performance of saturated and unsaturated fatty acids was also compared. The synthesis of lipoamides via direct amidation was conducted under reflux using a Dean-Stark trap and silica gel as the catalyst. On the other hand, the amidation of FAME was carried out without catalysts and solvent. Both reactions were run simultaneously for 18 hours at the same temperature. The reaction was monitored using TLC, and then the product was purified using column chromatography and characterized using FTIR and 1H NMR. The TLC data, FTIR, and 1H NMR spectra confirmed that both reaction pathways produced the same lipoamide as the product. Both reaction pathways were compatible with aromatic and nonaromatic amines and saturated and unsaturated fatty acids. The reaction yield of lipoamide from direct amidation was around 70-80% and two-fold higher than lipoamide synthesis via amidation of FAME. Therefore, direct amidation of fatty acid was preferred for the synthesis of lipoamides compared to via amidation of FAME.